Duterte: Delivering the Promised Peace to Mindanao - Singh, Bilveer (2016)
After years of starts-stops and derailment of peace agreements, the Philippines is today poised to make a peace breakthrough in strife-torn Muslim-dominated Mindanao in southern Philippines. The potential game changer is President-elect Rodrigo Duterte who has promised to break the past deadlocks in favour of a new federalism with a peace agreement with the Muslims in the south.